2002
DOI: 10.1097/00003226-200207000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Two Strains of Staphylococcus epidermidis to Contact Lenses

Abstract: Bacterial biofilm favors bacterial adhesiveness and colonization of soft CLs. Bacterial attachment was less in soft molding CLs (etafilcon A), which provide a more homogeneous and smoother surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Thus, for some surfaces of contact lenses that are more resistant to bacterial adhesion, the number of bacterial keratitis related to contact lenses might decrease [40]. On the basis of our results, it could be speculated that standard HEMA contact lenses would reduce the risk of corneal infection.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, for some surfaces of contact lenses that are more resistant to bacterial adhesion, the number of bacterial keratitis related to contact lenses might decrease [40]. On the basis of our results, it could be speculated that standard HEMA contact lenses would reduce the risk of corneal infection.…”
Section: Discussionmentioning
confidence: 76%
“…These conditions have included different strains/types of bacteria, contact lenses types, inoculum sizes, the nutritional content of media and the incubation time for adhesion to occur [9]. Viable plate count [10,11,12], number of cells adherent to parallel plate flow chambers [13], scanning electron microscopy [14], bioluminescent ATP assay [15], light microscopy [16], and assessment of the number of cells after radio-labeling [17] have been used to quantify microbial adhesion to lenses. Various solutions are used during adhesion experiments which include phosphate buffer saline (PBS) [18,19], which is nutritionally inert, and broths such as Tryptone Soy [20] or Mueller Hinton which are nutritionally rich.…”
Section: Introductionmentioning
confidence: 99%
“…18 McLaughlin-Borlace et al 18 have investigated bacterial biofilm formation from SCL and lens storage cases from 20 SCL wearers with microbial keratitis using SEM technique and showed that bacterial population analysis from biofilms and cornea from these 20 patients were similar and mostly composed of rods bacteria, cocci bacteria, fungi, and amoeba cysts. Garcia-Saenz et al 19 showed that an SE biofilm producer ATCC35984 strain exhibited higher adhesion to SCL than did an SE non-biofilm-producer ATCC12228 strain. Similarly, Gabriel et al 20 demonstrated that a slime producer #230022B SE strain showed a higher retention rate compared with a non-slime-producer #15072 to SCLs.…”
Section: Discussionmentioning
confidence: 99%